Health effects on workers exposed to engineered nanomaterials: Short review - Pereira, A (2017)
The huge increase in the nanotechnology industry has also resulted in an enormous growth in in the number of workers exposure to nanoparticles. Consequently, researches has been carried out regarding health and safety risks of engineered nanomaterials and the regulation of potential new hazards is a global concern. However, little is known about the impact of engineered nanomaterials in human health. This short review purpose is to identify the potential human health effects resulting from occupational exposure to engineered nanomaterials, supported on data base search. The article search revealed 5 studies on health effects performed in work-places and 14 in vitro and in vivo studies. Lung inflammatory effects, cytoxicity, oxidative stress and DNA damage were the most referred as potential health effects. However, more studies are still needed to obtain reliable data about nanomaterials effects on human health. (c) 2017 Taylor & Francis Group, London.